Computational Investigation of Zerumbone as an Inhibitor of TNF-alpha Using Molecular Dynamics and Molecular Docking Methods - Singh, Salam P.; Nongalleima, Khumukcham; Singh, Ningthoujam Indrajit; Chanu, Wahengbam Kabita; Singh, Thiyam Ramsing; Singh, Chingakham Brajakisor (Letters in Drug Design & Discovery, 2021)
Background: There are several reports on the anti-cancer property of zerumbone, such as in breast, cervical and ovarian cancer. But the investigation of the actual protein target has been the least concerned and there are few reports on the inhibitory effect of zerumbone against specific cancer-causing proteins and enzymes. Therefore, further investigation is required at a much deeper molecular level. Objective: This study aimed to determine the anti-proliferative activity of Zerumbone against cervical cancer cell and assess its TNF-α enzyme inhibitory action. Methods: The investigation emphasized the anti-cancer activity of zerumbone against HeLa cells and its subsequent TNF-α assay. Furthermore, computational studies on Zerumbone as an inhibitor of TNF-α were carried out using computational techniques such as docking and MD simulations. Results and Discussion: From the molecular docking analysis, it was observed and substantiated that the α,β-Unsaturated carbonyl scaffold is the main driving force for anti-cancer activity of zerumbone and inhibition of TNF-α. Conclusion: Zerumbone might be a potent anti-cancer agent targeting the HeLa cancer cell lines and inhibiting the TNF-α enzyme.
Keywords: docking